A Path Analysis on Adherence to Antiretroviral Therapy among HIV/ AIDS Patients at Dr. Moewardi Hospital, Surakarta using Health Belief Model - Dyah Ayu Agustin; Afiono Agung Prasetyo; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2018)
Background: HIV / AIDS (Acquired Immune Deficiency Syndrome) is still a health problem in the world including in Indonesia. Approximately 36.7 people are infected with HIV in the world and in Indonesia until March 2017 recorded 242,699 cases. The recorded amount does not reflect the real number in the community because HIV infection often does not show specific symptoms before entering the stage of AIDS. This study aimed to examine the application of the health belief model on adherence to antiretroviral therapy among HIV/ AIDS patients in Surakarta, Central Java.Subject and Method: This was a cross sectional study conducted at Dr. Moewardi Hospital, Surakarta, Central Java, on February 2018. A total sample of 284 HIV/AIDS patients was selected for this study by exhaustive sampling. The dependent variable was ARV Adherence. The independent variables were perceived susceptibility, perceived severity, perceived benefits, perceived barriers, cues to action, and self-efficacy. The data were collected using a questionnaire and analyzed by a path analysis.Results: Adherence directly increased with self-efficacy (b= 2.10; 95% CI = 0.85 to 3.34; p= 0.001), perceived benefit (b= 2.08; 95% CI= 1.15 to 3.00; p <0.001), and cue to action (b= 3.61; 95% CI= 0.86 to 6.36; p= 0.010) but decreased with higher perceived barrier (b= 2.08; 95% CI= 1.15 to 3.00; p<0.001). Adherence indirectly decreased with higher perceived severity and perceived susceptibility.Conclusion: Self-efficacy, perceived benefit, perceived barrier, and cue to action directly affect the adherence to antiretroviral therapy. Perceived severity and perceived susceptibility indirectly affect the adherence to antiretroviral therapy. Keywords: ARV adherence, perceived susceptibility, perceived severity, perceived benefits, perceived barriers, cues to action, self-efficacyCorrespondence: Dyah Ayu Agustin. School of Health Sciences Kendedes, Malang, East Java. Email: ayuagustin20@gmail.com. Mobile: +6281316337006.Journal of Health Promotion and Behavior (2018), 3(1): 48-55https://doi.org/10.26911/thejhpb.2018.03.01.05